Certain Family of Multivalent Functions Associated With Subordination - Mahmood, Zainab H.; Shihab, Buthyna N.; Jassim, Kassim A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The main objectives of this pepper are to introduce new classes. We have attempted to obtain coefficient estimates, radius of convexity, Distortion and  Growth theorem and other related results for the classes